Greek Landrace Flours Characteristics and Quality of Dough and Bread - Adriana Skendi; Maria Papageorgiou; Maria Irakli; Stefanos Stefanou (Foods, 2023)
Besides organic growing, ancient wheats and landraces are attracting the attention of scientists who are reassessing the healthy and dietary properties attributed to them by popular tradition. A total of eleven wheat flours and whole meal samples were analyzed, of which, nine originated from the organic farming of five Greek landraces (one einkorn, one emmer, two durum, and one soft wheat) and a commercial organically grown emmer cultivar. Two commercial conventional flours of 70% and 100% extraction rate were examined for comparison purposes. Chemical composition, micronutrients, phenolic profile, and quantification, and antioxidant activity of all samples were determined. Moreover, dough rheology and breadmaking quality were studied; Flours from local landraces were higher in micronutrients, phenolic content, and antioxidant activity than the commercial samples. The 90% extraction flour of the landrace, besides the highest protein content (16.62%), exhibited the highest content of phenolic acids (19.14 μg/g of flour), whereas the commercial refined emmer flour was the lowest (5.92 μg/g of flour). The same milling of the einkorn landrace also showed a higher specific volume (1.9 mL/g vs. 1.7 mL/g) and lower bread crumb firmness than the whole meal commercial emmer sample (33.0 N vs. 44.9 N). The results of this study showed that the examined Greek wheat landraces could be considered as a possible source of microelements, phenolics, and antioxidants with a beneficial effect in human health, and by using an appropriate breadmaking procedure, they could produce high-quality breads.